The marine fishes of West Africa - Fowler, H.W. (New York, New York The American Museum of Natural History, 1936)
Bulletin of the American Museum of Natural History, vol. LXX part. 1
Keywords: Marine fishes--West Africa; Marine fishes--Identification.